Mechanism of Concussion in Sports 2014
DOI: 10.1520/stp155220120159
|View full text |Cite
|
Sign up to set email alerts
|

For ASTM F-08: Protective Capacity of Ice Hockey Player Helmets against Puck Impacts

Abstract: Many studies have assessed the ability of hockey helmets to protect against falls and collisions, yet none have addressed the injury risk associated with puck impacts. Thus, the purpose of this study was to document the capacity of a typical vinyl nitrile ice hockey helmet to reduce head accelerations and brain deformation caused by a puck impact. A bare and a helmeted Hybrid III male 50 th percentile headform were struck with a puck three times to the forehead at 17, 23, 29, and 35 m/s using a pneumatic puck … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…These results are consistent with previous research, as ice hockey helmets have been found to reduce engineering parameters for low velocity puck impacts but not for high velocities. 49,66 However when MPS was assessed, the ice hockey helmet that was tested was unable to reduce MPS to below the levels of concussion and TBI reported in the literature 32,60,62,88 except in the site 1 at 40 m/s and site 2 at 20 m/s conditions. As such, the tested ice hockey helmet adequately reduced this engineering parameter in a limited number of conditions.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…These results are consistent with previous research, as ice hockey helmets have been found to reduce engineering parameters for low velocity puck impacts but not for high velocities. 49,66 However when MPS was assessed, the ice hockey helmet that was tested was unable to reduce MPS to below the levels of concussion and TBI reported in the literature 32,60,62,88 except in the site 1 at 40 m/s and site 2 at 20 m/s conditions. As such, the tested ice hockey helmet adequately reduced this engineering parameter in a limited number of conditions.…”
Section: Discussionmentioning
confidence: 94%
“…The mass of the impacting arm is similar to that calculated for shoulder-to-head impacts in ice hockey reconstructions. 66 The end of the impacting arm was fitted with two different strikers to simulate stiff elbow collisions and shoulder-to-head impacts. A striker consisting of hemispherical nylon pad with a 35.71 ± 0.01 mm thick vinyl nitrile 602 foam disk underneath was used to simulate stiff elbow collisions (Fig.…”
Section: Equipmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies examined helmet efficacy against concus-sion through in simulacra and in silico impact tests. 5,47,57,68,69,83,85,87,89,98 These studies are summarized in Table 1. Two of the 10 studies observed military helmet efficacy against concussion and blast injury in the ACH.…”
Section: Impact Simulation Of Concussionmentioning
confidence: 99%
“…Ice hockey, baseball, and speed skating helmets were all shown to have significant risks of concussion by impact velocities or acceleration directions. 87,89 Karton et al found that bicycle, ice hockey, and speed skating helmets all consistently presented a greater than 50% probability of players wearing these helmets sustaining a concussion at the mean peak rotational accelerations. 47 From striking-pendulum impact tests, O'Sullivan et al showed that standard Taekwondo helmets do not protect against low-energy (50g) and high-energy (150-g) head impacts that can induce concussion.…”
Section: Impact Simulation Of Concussionmentioning
confidence: 99%